2006
DOI: 10.1115/1.2386207
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Size Effect on Friction Conditions in Microextrusion—Part I: Microextrusion Experiments and Analysis

Abstract: Microforming is a relatively new realm of manufacturing technology that addresses the issues involved in the fabrication of metallic microparts, i.e., metallic parts that have at least two characteristic dimensions in the sub-millimeter range. The recent trend towards miniaturization of products and technology has produced a strong demand for such metallic microparts with extremely small geometric features and high tolerances. Conventional forming technologies, such as extrusion, have encountered new challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 19 publications
2
62
0
Order By: Relevance
“…It is revealed that the coating of DLC-plasma can significantly decrease the friction, while the coatings of TiN and CrN increase the friction. A similar study was done by Krishnan et al [78] using brass in micro forward extrusion process, but different results were obtained. Their results indicate that the coatings of DLC-Si, CrN and TiN can reduce the extrusion force.…”
Section: Interfacial Frictionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is revealed that the coating of DLC-plasma can significantly decrease the friction, while the coatings of TiN and CrN increase the friction. A similar study was done by Krishnan et al [78] using brass in micro forward extrusion process, but different results were obtained. Their results indicate that the coatings of DLC-Si, CrN and TiN can reduce the extrusion force.…”
Section: Interfacial Frictionsupporting
confidence: 63%
“…4.37a. To overcome the difficulty in part ejection, separating the extrusion die into two halves was proposed by Krishnan et al [78] and the authors of this monograph. However, such design could lead to the formation of flash at the parting line, as shown in Fig.…”
Section: Interfacial Frictionmentioning
confidence: 98%
See 1 more Smart Citation
“…Especially if the non-uniform pressure distribution was Although these applied researches on the field of dry-microforming are well developed for the practical application, the basic research on the dry friction behaviour during microforming was quite few and it was only worked for bulk metal forming (Vollertsen et al, 2009). Krishnan et al investigated the scale effect on dry friction by scaled forward extrusion test of brass (Cu:Zn 70:30) with the scale range of 0.57-1.33mm in outer diameter of extruded pin (Mori et al, 2007;Krishnan et al, 2007). In addition, the other author conducted the scaled ring compression test of CuZn15 alloy with different grain size.…”
Section: Introductionmentioning
confidence: 99%
“…First application was reported by Yang et al, who applied to the micro-extrusion die using pulse plasma chemical vapor deposition (CVD) method [4]. Similarly, the friction properties of DLC coated microdies were followed by Krishnan et al, for micro-extrusion process [5] and by Fujimoto et al for microbending process [6], Aizawa et al for micro-bending with ironing [7], and Hu et al [8] and by Wang et al [9] for micro-deep drawing process.…”
Section: Introductionmentioning
confidence: 99%